Environmental transport processes - Logan, Bruce E. (Hoboken, N.J. : John Wiley & Sons, 2012)
'Developed as a reference for transport phenomena courses, this completely revised second edition of Environmental Transport Processes provides a readable and approachable treatment of environmental systems. The text features a unique combination of material from different fields (mass transport, kinetics, wastewater treatment, unit processes) and includes pertinent literature not available in any other texts. Rich with examples and problems to help reinforce students? learning, the updated edition addresses new and emerging topics, such as non-aqueous phase liquids (NAPLs), the subject of aggregates, and biofilm kinetic models merged with mass transport concepts'--
'The second edition of Environmental Transport Processes has the same general format as the first edition. The book is intended to serve as a reference for a course on transport phenomena. The book uses many examples and provides a large number of problems that students can use to learn the material. Most of the material from the first edition has stayed relevant, however some sections of the book are now out of date and require to be addressed using more modern approaches'--
Includes index.
Keywords: Environmental chemistry; Transport theory; Environmental engineering